2019
DOI: 10.1111/1467-8462.12319
|View full text |Cite
|
Sign up to set email alerts
|

State of Confusion: Economic Policy Uncertainty and International Trade and Investment

Abstract: Uncertainty about economic policy in Australia and the United States has increased episodically since the Global Financial Crisis. Existing research focuses on the effects on economic activity, employment and investment. I extend this work to examine the effect of policy uncertainty on global trade volumes, industrial production and cross-border trade and investment for Australia and the United States. Australia's relative resilience to policy uncertainty shocks reflects a larger role for the exchange rate in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…Several studies have confirmed that EPU has negative effects on firms’ research and investment, employment, consumer behavior, stock market performance, crude oil price, exchange rate, global trade growth, etc. [ 35 42 ]. The on-going COVID-19 pandemic raises global economic uncertainty, leading to agricultural trade disruption which raises food prices and reduces food security globally [ 43 , 44 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several studies have confirmed that EPU has negative effects on firms’ research and investment, employment, consumer behavior, stock market performance, crude oil price, exchange rate, global trade growth, etc. [ 35 42 ]. The on-going COVID-19 pandemic raises global economic uncertainty, leading to agricultural trade disruption which raises food prices and reduces food security globally [ 43 , 44 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, economic uncertainty increases the volatility of commodities, meaning that potential uncertainty permanently affects the volatility of commodities, whereas the impact of observable uncertainty is short-lived or even insigni cant (Bakas and Triantafyllou 2018). Furthermore, EPU is also detrimental to nancial stability (Phan et al 2020) and global trade volumes (Kirchner 2019).…”
Section: Economic Policy Uncertainty and Green Technology Innovatiomentioning
confidence: 99%
“…The economic motivation for each of these variables should be self‐explanatory. The Australian Economic Policy Uncertainty Index is included partly to account for the effect federal elections and political uncertainty might have on confidence, as well as offshore uncertainty, which is highly correlated with domestic policy uncertainty (Kirchner ).…”
Section: A Model Of Consumer Sentimentmentioning
confidence: 99%
“…Sentiment has a surprisingly low elasticity with respect to the Australian Economic Policy Uncertainty Index, although a statistically significant relationship. This likely reflects a recent uptick in measured uncertainty on global concerns that may not have resonated strongly with consumers (Kirchner ). Dwelling values as a measure of housing wealth also have a strong influence on sentiment.…”
Section: A Model Of Consumer Sentimentmentioning
confidence: 99%